Integration of Wind Energy Conversion System with Microgrid and Utility - Fan, Y.; Goyal, M.; Ghosh, Arindam; Shahnia, Farhad (Institute of Electrical and Electronics Engineers (IEEE), 2014)
An integration of a Permanent Magnetic Synchronous Generator (PMSG) based Wind Energy ConversionSystem (WECS) into a microgrid is discussed in this paper. A back-to-back Voltage Source Converter (VSC) is employed for the power conversion from the PMSG to the AC grid. The Sinusoidal Pulse Width Modulation (SPWM) technique is adopted for the Wind-side Converter (WSC), while for the Gridside Converter (GSC), Space Vector Pulse Width Modulation (SVPWM) is applied. A Maximum Power Point Track (MPPT) control scheme called the Optimal Power Control (OPC) is used for the WSC to draw the maximum power from wind energy. The DC voltage of the back-to-back converter is controlled by the GSC. The microgrid contains a microturbine and a diesel generator, along with loads. The power flow from the WECS to the microgrid is controlled through another back-to-back converter. Four different cases are studied to validate the performance of the WECS integration with the microgrid system.